Xie Zhuo Tiao Zhi formula ameliorates chronic alcohol-induced liver injury in mice - Chang, Kaixin; Guo, Rui; Hu, Wenbo; Wang, Xuezhu; Cao, Feiwei; Qiu, Jiannan; Li, Jiaomei; Han, Qiang; Du, Zhongyan; Dou, Xiaobing; Li, Songtao (Frontiers in Pharmacology, 2024)
This study aimed to evaluate the protective role and potential mechanisms of Xie Zhuo Tiao Zhi decoction (XZTZ) on alcohol-associated liver disease (ALD). XZTZ significantly alleviated alcoholinduced liver dysfunction, based on histological examinations and biochemical parameters after 4week administration. Mechanically, alcohol-stimulated hepatic oxidative stress was ameliorated by XZTZ, accompanied by the improvement of Nrf2/Keap1 expression and alcohol-activated phosphorylation of pro-inflammatory transcription factors, including JNK, P38, P65, and IκBα, were rescued by XZTZ. In conclusion, XZTZ demonstrates potential in alleviating alcohol-induced liver injury, oxidative stress, and inflammation possibly through modulation of Nrf2/Keap1 and MAPKs/NF-kB signaling pathways, suggesting its potential as a therapeutic option for patients with alcoholic liver disease.